The SILCC project: IV. Impact of dissociating and ionising radiation on the interstellar medium and Hα emission as a tracer of the star formation rate - Peters, Thomas; Glover, Simon; Klessen, Ralf S.; Baczynski, Christian (Arxiv, 2016)
We present three-dimensional radiation-hydrodynamical simulations of the impact of stellar winds, photoelectric heating, photodissociating and photoionising radiation, and supernovae on the chemical composition and star formation in a stratified disc model. This is followed with a sink-based model for star clusters with populations of individual massive stars. Stellar winds and ionising radiation regulate the star formation rate at a factor of ~10 below the simulation with only supernova feedback due to their immediate impact on the ambient interstellar medium after star formation. Ionising radiation (with winds and supernovae) significantly reduces the ambient densities for most supernova explosions to rho < 10^-25 g cm^-3, compared to 10^-23 g cm^-3 for the model with only winds and supernovae. Radiation from massive stars reduces the amount of molecular hydrogen and increases the neutral hydrogen mass and volume filling fraction. Only this model results in a molecular gas depletion time scale of 2 Gyr and shows the best agreement with observations. In the radiative models, the Halpha emission is dominated by radiative recombination as opposed to collisional excitation (the dominant emission in non-radiative models), which only contributes ~1-10 % to the total Halpha emission. Individual massive stars (M >= 30 M_sun) with short lifetimes are responsible for significant fluctuations in the Halpha luminosities. The corresponding inferred star formation rates can underestimate the true instantaneous star formation rate by factors of ~10.